2016
DOI: 10.1371/journal.ppat.1005685
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Antibiotic Leucinostatins in Bio-control Fungus Purpureocillium lilacinum and Their Inhibition on Phytophthora Revealed by Genome Mining

Abstract: Purpureocillium lilacinum of Ophiocordycipitaceae is one of the most promising and commercialized agents for controlling plant parasitic nematodes, as well as other insects and plant pathogens. However, how the fungus functions at the molecular level remains unknown. Here, we sequenced two isolates (PLBJ-1 and PLFJ-1) of P. lilacinum from different places Beijing and Fujian. Genomic analysis showed high synteny of the two isolates, and the phylogenetic analysis indicated they were most related to the insect pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
116
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 108 publications
1
116
0
8
Order By: Relevance
“…EfM3.055320 was only expressed in the in planta comparisons and is a homologue of Cu/Zn superoxide dismutase from Claviceps purpurea [6] which are involved in reducing superoxide radicals generated by host plant defence mechanisms. EfM3.079420 is a homologue of a fungal hydrophobin domain-containing protein in Pochonia chlamydosporia [62].…”
Section: Resultsmentioning
confidence: 99%
“…EfM3.055320 was only expressed in the in planta comparisons and is a homologue of Cu/Zn superoxide dismutase from Claviceps purpurea [6] which are involved in reducing superoxide radicals generated by host plant defence mechanisms. EfM3.079420 is a homologue of a fungal hydrophobin domain-containing protein in Pochonia chlamydosporia [62].…”
Section: Resultsmentioning
confidence: 99%
“…() reported that C. globosum produced a secondary metabolite that reduced in vitro growth of the northern corn leaf blight pathogen, Setosphaeria turcica , and inhibited development of the disease on detached corn leaves. Likewise, P. lilacinum (Wang et al ., ) and P. citrinum (Melouk & Akem, ; Park et al ., ) produced inhibitory secondary metabolites in vitro . Lan et al .…”
Section: Discussionmentioning
confidence: 99%
“…Putative heat‐labile enterotoxin genes were retrieved for 14 entomopathogenic fungi (one strain per species) (Supporting Information Table ): Metarhizium anisopliae ARSEF23 (24 genes), M. acridum CQMa 102 (three genes) (Pattemore et al., ); M. album ARSEF1941 (12 genes), M. brunneum ARSEF3297 (32 genes), M. guizhouense ARSEF977 (32 genes), M. majus ARSEF297 (32 genes) (Hu et al., ); M. rileyi RCEF4871 (three genes), Isaria fumosorosea ARSEF2679 (five genes), Aschersonia aleyrodis RCEF2490 (14 genes), Cordyceps confragosa RCEF1005 (six genes), C. brongniartii RCEF3172 (30 genes) (Shang et al., ), Cordyceps militaris CM01 (one gene, Zheng et al., ), Beauveria bassiana ARSEF2860 (six genes, Xiao et al., ); and Ophiocordyceps sinensis Co18 (13 genes, Xia et al., ). We also included putative heat‐labile enterotoxin sequences from two nematode‐killing fungi: Purpureocillium lilacinum PLBJ‐1 (two genes, Wang et al., ) and Pochonia chlamydosporia 170 (four genes). Orthologs between these sequences and the putative enterotoxins of O. unilatealis species studied here were identified.…”
Section: Methodsmentioning
confidence: 99%